La evaluación de los aprendizajes en la formación integral de los niños y niñas del sexto y séptimo año de educación básica de la Escuela "Río Ucano" de la parroquia General Farfán del cantón Lago Agrio, provincia de Sucumbíos en el período lectivo 2010 - 2011 - Guamán Pilataxi, Xavier Núñez (2011)
To start this research work was carried out a thorough analysis of the various problems afflicting the education sector and among them, in my personal opinion after solicit opinions to some education professionals, decided to work on the topic: "the learning assessment in the overall education of children in the Sixth and Seventh Year Basic Education School Rio Ucano. This is an issue that becomes very relevant today, all while working with another vision with other educational paradigms in which children have to develop skills, some questions arise as a result will be that teachers are truly developing the skills and contributing in their comprehensive training, how to know, then it is clear, only through assessment of learning we can see whether or not achieving the objective, such under the problem that guided this study is "How to bring instruments evaluation for the integral development of children under the Sixth and Seventh Year Basic Education Ucano River school "educational institution that counts in these 2 years of basic education with 95 students and 7 teachers. Once identified the problem began with the research literature on this subject, which led me to study what new educational paradigms and they say each of them with regard to the evaluation, what are the processes of learning assessment, different types of evaluation exist, then I know that evaluation is an "integral, permanent, systematic and scientific" immersed in the process of teaching and learning as a key element of the aircraft and met the various techniques and tools assessment of learning. Known theoretical and conceptual framework, it was easy to hypothesize, "the assessment of learning contributes to the integral development of children in the sixth and seventh year of basic education school in the parish Ucan River General Farfán the Lago Agrio Canton province of Sucumbios for school year 2010 - 2011 "and this guided the research, led the completion and implementation of surveys that were designed with closed questions and questionnaires administered to students and teachers. Once they had all the empirical data was a statistical and interpretive analysis of information, allowing it to reach conclusions and recommendations, to testing the hypothesis, which incidentally was positively tested with what is recognized that evaluation is a strategy of educational work valid and more efficient to guide the development of children, as a result of this analysis and hypothesis testing comes the urgent need to write a didactic instructional techniques and learning assessment tools, to be delivered to the school institution Ucan River gave all facilities to complete research work, which I extend my deepest gratitude.